Persyaratan Klaim Biaya Overhead dan Mekanisme Penyelesaian Sengketa Konstruksi di Indonesia: Suatu Kajian Normatif - Qadri, Qadri; Sami’an, S.; Saputro, Adi (SIGn Jurnal Hukum, 2024)
Overhead cost claim disputes are a crucial issue in Indonesia’s construction industry. Therefore, this research aims to comprehensively analyze the legal aspects of overhead cost claims in construction contracts in Indonesia, encompassing the legal basis, types of claimable costs, legal conditions triggering claims, claim submission requirements, calculation methods, and dispute resolution mechanisms. A normative juridical method is employed to achieve this objective, using a statute, case, and conceptual approach. Data is sourced from statutory regulations, construction contract standards, jurisprudence, and legal literature and then analyzed qualitatively. Substantively, this research finds that the legal basis for overhead cost claims in Indonesia involves a complex interaction between Law Number 2 of 2017, Government Regulation Number 22 of 2020, the Civil Code, and contract standards such as FIDIC. Furthermore, overhead claims must be based on wanprestasi (breach of contract), force majeure, or variation orders and must meet the requirements of notification, documentation, accountable calculation, and causality. In terms of calculation, the accepted method must be by the principle of compensation. As for dispute resolution, it can be through mediation, conciliation, arbitration, or litigation, with the caveat that the selection of a mechanism depends on a case-by-case analysis. Overall, this research provides a comprehensive understanding of the legal aspects of overhead cost claims in construction contracts in Indonesia.